Enhancement of 17α-hydroxyprogesterone production from progesterone by biotransformation using hydroxypropyl-β-cyclodextrin complexation technique - Manosroi J. (2014)
An enhancement of 17α-hydroxyprogesterone (17α-HP) production from progesterone by biotransformation using hydroxypropyl-β-cyclodextrin (HPβCD) complexation together with aeration and sonication technique was demonstrated. The progesterone-hydroxypropyl-β-cyclodextrin complex was prepared by co-evaporation method. The percentage yield of 17α-HP from P of 11.26 ± 0.64% at 24 h was observed in Curvularia lunata ATCC 12017. In the complex form of P, together with sonication at 40 kHz for 5 s and aeration, the yield of 17α-HP was increased to 72.92 ± 4.28% which was about 6.5 and 1.3 times of that from the uncomplexed (P) and the complexed (PC), respectively without sonication and aeration. The increased aqueous solubility of P by complexation with HPβCD was the main factor which increased the yield of 17α-HP, while aeration had more effect on P than PC. Sonication did not significantly increased the yield of the product from both P and PC. When both aeration and sonication were used in the PC system, the product yield was increased significantly more than that from P. The result from this study can be applied for the biotransformation of other poor aqueous soluble precursors. © 2008 Elsevier Ltd. All rights reserved.